2018
DOI: 10.1609/aaai.v32i1.12328
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Temporal Graph Convolutional Networks for Skeleton-Based Action Recognition

Abstract: Dynamics of human body skeletons convey significant information for human action recognition. Conventional approaches for modeling skeletons usually rely on hand-crafted parts or traversal rules, thus resulting in limited expressive power and difficulties of generalization. In this work, we propose a novel model of dynamic skeletons called Spatial-Temporal Graph Convolutional Networks (ST-GCN), which moves beyond the limitations of previous methods by automatically learning both the spatial and temporal patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1,498
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 3,154 publications
(1,506 citation statements)
references
References 18 publications
4
1,498
0
4
Order By: Relevance
“…This indicates that topological graph representations can be more suitable for representing the skeleton data. As a result, many GNN and GCN-based HAR methods [186], [221] have been proposed to treat the skeleton data as graph structures of edges and nodes.…”
Section: Gnn or Gcn-based Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This indicates that topological graph representations can be more suitable for representing the skeleton data. As a result, many GNN and GCN-based HAR methods [186], [221] have been proposed to treat the skeleton data as graph structures of edges and nodes.…”
Section: Gnn or Gcn-based Methodsmentioning
confidence: 99%
“…Si et al [221] proposed a spatial reasoning network, followed by RNNs, to capture the high-level spatial structural and temporal dynamics of skeleton data. Shi et al [222] represented the skeleton as a directed acyclic graph to effectively shown in [186], [194], [209], [218].…”
Section: Gnn or Gcn-based Methodsmentioning
confidence: 99%
See 3 more Smart Citations